Development with an Ecological Perspective Focusing on Wetlands of Kadamakudy Panchayat, Kochi. (2016) - Deepak, V.
Abstract: Kochi is a rapidly growing commercial, industrial and trading centre of Kerala. Due to the tremendous growth and urbanization, the density of population in city is increasing every year. These factors have resulted in land use stresses, reducing open areas especially wetlands[1] in Kochi city for the past decades through land reclamation and encroachments. Again, anthropogenic activities like industrialisation, improper management of sewage and other solid waste lead to degradation of these ecosystems. This study discusses about the unique status of wetlands of Kadamakudypanchayat of Kochi with its Pokkali fields[2], fish farms. It also tries to propose guidelines, strategies and action plan at site specific level for development, conserving its wetlands along with its wise use in an ecological perspective keeping in mind the rapid urbanisation.